Evidence for the decay Bs0→Ds(*)Ds(*) and a measurement of ΔΓsCP/Γs - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
We search for the semi-inclusive process Bs0→Ds(*)Ds(*) using 2.8fb-1 of pp̄ collisions at s=1.96TeV recorded by the D0 detector operating at the Fermilab Tevatron Collider. We observe 26.6±8.4 signal events with a significance above background of 3.2 standard deviations yielding a branching ratio of B(Bs0→Ds(*)Ds(*))=0.035±0.010(stat. )±0.011(syst.). Under certain theoretical assumptions, these double-charm final states saturate CP-even eigenstates in the Bs0 decays resulting in a width difference of ΔΓsCP/Γs=0.072±0.021(stat.) ±0.022(syst.). © 2009 The American Physical Society.